2005
DOI: 10.1093/ndt/gfh677
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity regulates the aquaporin-2 promoter independently of arginine vasopressin

Abstract: These findings indicate that hypertonicity regulates AQP-2 promoter activity via an AVP-independent mechanism, and that the tonicity-responsive element resides between the -6.1 and -4.3 kb 5'-flanking region of the AQP-2 gene, in which the structure and mechanism of response to hypertonicity could be distinct from those of TonE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
3
35
1
Order By: Relevance
“…This escape phenomenon has been shown to depend on both nitric oxide and prostaglandin production (26). There is evidence that tonicity may be a significant signal (16,19). However, chronic furosemide treatment, which will also wash out the medullary gradient, did not decrease AQP2 levels in vivo (25, 37).…”
mentioning
confidence: 99%
“…This escape phenomenon has been shown to depend on both nitric oxide and prostaglandin production (26). There is evidence that tonicity may be a significant signal (16,19). However, chronic furosemide treatment, which will also wash out the medullary gradient, did not decrease AQP2 levels in vivo (25, 37).…”
mentioning
confidence: 99%
“…Mutations in components of this pathway, especially in AVPR2 and AQP2, cause defects in urine concentration manifested as nephrogenic diabetes insipidus (NDI) (23). While AVP/AVPR2 signaling can regulate the long-term expression of AQP2 (35), regulation of AQP2 by AVP-independent mechanisms has also been reported (14,20,42).Although the hypertonic environment within the kidney allows for reabsorption of water, it also subjects cells to a potentially lethal osmotic stress. The cellular response that permits cells of the renal medulla to adapt and survive within a hypertonic environment is mediated by the tonicity-responsive enhancer binding protein (TonEBP)/nuclear factor of activated T cells (NFAT)5 transcription factor (13).…”
mentioning
confidence: 99%
“…dDAVP Dependence of Tonicity-induced AQP2 Transcription-Tonicity can change AQP2 abundance independent of AVP in vivo (7,9). To test whether an AVP-independent effect of tonicity on AQP2 expression is also observed in our cells, mpkCCD-AQP2-3.0-luc cells were again treated with dif-FIGURE 2.…”
Section: Mpkccd Cells As a Model For Tonicity-induced Aqp2mentioning
confidence: 99%
“…In a rat animal model, it has been shown that the onset of this escape coincides with a decrease in the AQP2 expression in the renal collecting duct (6). Hypotonicity and/or volume expansion have been proposed to mediate this AVP-independent direct regulation of AQP2 expression (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation